Consequences of the reintroduction of regionally extinct mammals for vegetation composition and structure at two established reintroduction sites in semi‐arid Australia. (16th March 2021) - Kemp, Jeanette E.; Jensen, Rigel; Hall, Michelle L.; Roshier, David A.; Kanowski, John
Abstract: Australia has lost a substantial proportion of its small to medium‐sized mammals since European colonisation. Given the passage of time since local extinctions – decades to more than a century for much of the continent – the consequences of these changes for vegetation are poorly known. In this study, we take advantage of two well‐established mammal reintroduction projects in southern inland Australia to examine the ecological consequences for vegetation of re‐established mammal populations. The study is based on replicated surveys inside and outside fenced reintroduction sites, with treatments characterised by varying presence, absence and composition of reintroduced mammals, feral predators and feral herbivores. We found a suite of differences in vegetation between reintroduction sites and matched controls, with generally lower richness inside reintroduction sites (with one exception). Other compositional differences varied by location, with some functional groups – herbaceous chenopods, shrubby chenopods, introduced geophytes and low shrubs – and a few individual chenopod species – being less frequent inside the reintroduction site at one location. At the same site, mistletoes and orchids were less abundant inside than outside the reintroduction site. Structural differences included a higher percentage of bare ground inside, and a higher ground layer for one inside treatment versus outside. Although the absence of baseline data and replicated temporal data limits inference as to causal factors, many of the results are consistent with data from other reintroduction sites. Some results, especially those for geophytes, mistletoes and some chenopods, may indicate long‐term consequences for those taxa. Whilst predator‐fencing substantially contributes to prevention of extinction of highly threatened mammals, some environmental trade‐offs are inevitable. Nonetheless, given the aims of reintroductions include re‐constructing natural ecosystem processes, the resulting changes to vegetation require ongoing investigation and further monitoring. Abstract : This study examines the consequences of mammal reintroduction projects for vegetation using two established sites in southern inland Australia. The results showed several significant differences inside versus outside predator‐proof exclosures, including differences in species richness and frequency of plant functional groups and species. The results are placed in the context of more than a century of environmental degradation and change.